Overview of Adversity Quotient on Students who are Compiling Thesis at University: Gambaran Adversity Quotient pada Mahasiswa yang Sedang Menyusun Skripsi di Universitas - Ibrahim, Iqbal Malik; Fahmawati, Zaki Nur (Universitas Muhammadiyah Sidoarjo, 2023)
This research is motivated by the problems that are often experienced by students in improving their thesis and has the aim of knowing the description of the adversity quotient of students who are writing thesis on the faculty of psychology and education, Muhammadiyah University of Sidoarjo. This research uses descriptive quantitative research. The population is 650 FPIP students who are compiling a thesis using the Krejcie table and get a sample of 242 students who are taken using the Simple Random Sampling technique. Data retrieval using the adversity quotient scale adapted by Maulana (2020) which refers to Stoltz's (2005) theory includes the following aspects: (CO2RE) control, ownership and origin, reach, endurance and the reliability of Cronbach Alpha is 0.858. The analysis of this research uses JASP vers 0.15. The results of this study indicate that men have a high adversity quotient of 71.66%, while women have a high adversity quotient of 68.68%.